THE EFFECT OF THE LEVEL OF UNDERSTANDING AND THE ROLE OF THE AGENT IN RAISING THE INTEREST OF THE PUBLIC IN THE INSURANCE COMPANY PT. PANINDAI-ICHILIFE GA UNITY MEDAN - Al Firah; Lulu Agnes; Ananda Sulfiani (Universitas Dharmawangsa Medan, 2023)
ABSTRACT This research aims to identify and analyze the influence of the level of understanding and the role of agents in increasing the interest of customers of PT. PaninDai-Ichilife Ga Unity Medan. Data collection methods through observations, interviews, documentation, questionnaires. This research uses double linear regression analysis techniques with quantitative data. The sample consisted of 60 respondents who were customers of P.T. PaninDai-IchiLife Ga Unity Medan. Test results t (partially), agent level understanding variable obtained thitung > ttable (2,105 > 2,002) with a significance value > 0,1 then Ho accepted and Ha rejected means the level of agent understanding partially influenced significantly on customer interests. Test result t (partly), agent role variable received thitung> ttable size (2,740 > 2,001), with significance values > 0,5 then Ho received and Ha denied. Whereas if the value of significance < 0,5 then ho denied and Ha received means the role of agent partially had a significant influence on the customer interest. Test results F (simultaneously), customer interest variable Obtained F > F Calculation Table (8,898 > 3,16) showed that independent variables (level of understanding agent and agent role) significantly contributed significantly to customer dependent variable (responsible) then H0 and Ha accepted, meaning that there was an influence between both independent variable and variable dependent.Keywords: Understanding level, Agent role, Customer interests, Insurance